Visualization of Science Literacy in Learning Based on STEM at Natural Schools, Bengkulu Indonesia - Widya Kartika Sari; Dodo Sutardi; Bentar Priyopradono (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2022)
One of the problems of education in Indonesia today is the low literacy of mathematics, science and reading. STEM (Science Technology Engineering Math) education is an effort made by almost all countries to improve scientific, technological, and mathematical literacy. Indonesia developed the 2013 curriculum to improve literacy. Several research results on STEM education in Indonesia conclude that STEM education has been well understood by most teachers in Indonesia. However, in the implementation of learning, not many have implemented it. This paper will visualize the implementation of STEM education in improving students' literacy skills, and help achieve the Alam Bengkulu school's vision, "Being a reference for the world of education in Bengkulu in forming a generation that loves science." The material is packaged in multimedia in the form of text, animation, sound, and video. , in accordance with the demands of learning materials. The research was conducted at the Bengkulu Nature School. The goal is to popularize the implementation of STEM education which has not been widely applied by teachers. For example, implementing learning by integrating Science, Technology, Engineering and Mathematics, increasing scientific literacy, through local content in natural schools.